'A New Interpretation of Plato's Socratic Dialogues - Kahn, Charles (2000)
A study of the remainsof the other Socratic authors, and of Eschines in particular, makes clear that this dialogue form was essentially a genre of fictional "conversations with Socrates". freely invented even when the interlocutors were historical. Hence it is a mistake to regard Plato's earlier dialogues as a report of the philosophy of the historical Socrates. The present interpretation aims toreplace the notion of a "Socratic period" in Plato's philosophical development with a more unified View of Plato's work as a whole. Hence the notion of "prolepsis" is utilized to suggest that most of the so-called "Socratic-dialogues"are Written (and intended to be read) from the point of View of the socalled "middle dialogues".